The exportation of terrorism through Emni: A review of the orchestrated attacks from Syria to Libya under the label of the Islamic State's external operations service (Journal of the Spanish Institute for Strategic Studies, 2023)
The present study seeks to explain the creation of the Islamic State's (IS) external operations service by linking the Franco-Belgian unit of Amn al Kharji (Emni) with the Libyan-Tunisian contingent of the Katibat al Battar al Libiyya (KBL) militia. This starting premise is sustained by the theory that Emni and KBL merged into a single entity, thus explaining that the first attacks carried out under the label of IS's external operations service were orchestrated from Syria, while the second wave of attacks instigated from Libya coincided with the loss of territory in Syria and the return of many KBL fighters to Libya.In order to better convey the results of the research, we have proceeded to briefly outline the origins behind the creation of an intelligence service within the Islamic State, and then analyze, from a relational perspective, the existing links between the members who conformed the external operations unit of IS and the people who integrated the commandos of the attacks that struck Europe and Tunisia between 2014 and 2017.
Keywords: terrorism; Islamic State (IS); IS's external operations service; Amn al Kharji (Emni); Katibat al Battar al Libiyya (KBL)